Redistricting litigation : an overview of legal, statistical, and case-management issues - Clarke, Bruce, 1945- (LLMC-digital (Series), 2002)
This monograph has three chapters. Chapter 1, on the law of redistricting, is the major chapter. This chapter examines the recurring legal-political issues at play in redistricting cases, comments briefly on evidentiary issues, discusses vote dilution cases brought pursuant to section 2 of the Voting Rights Act of 1965, and describes cases involving redistricting and the Equal Protection Clause. Chapter 2 discusses statistical evidence of racially polarized voting, and Chapter 3 discusses some of the major case-management challenges presented by redistricting cases. This monograph is an excellent introduction to the field of redistricting litigation, and provides a wealth of links to underlying case law for further research.